2010
DOI: 10.1063/1.3422324
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous velocity and pressure measurements using luminescent microspheres

Abstract: Using the technique of modified rapid lifetime determination, pressure-sensitive microspheres, known as PrSBeads, were used to make quantitative oxygen measurements over two-dimensional areas within gaseous flows. Aerosolized PrSBeads in carrier gases of varying oxygen concentrations demonstrated point measurement precisions on the order of 0.1%-1%. A charge-coupled device featuring a double image frame (DIF) feature was used to make spatially resolved pressure measurements within gas phase flows. Errors on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Im et al [116], Kimura et al [115,118], and Kim et al [114] fabricated pressure sensitive microbeads using PtOEP. Im et al [116] fabricated polystyrene beads with the incorporation of pressure sensitive and insensitive luminophores.…”
Section: Dopant Dyes For Other Application (Partial Pressure Of Oxygen)mentioning
confidence: 99%
See 1 more Smart Citation
“…Im et al [116], Kimura et al [115,118], and Kim et al [114] fabricated pressure sensitive microbeads using PtOEP. Im et al [116] fabricated polystyrene beads with the incorporation of pressure sensitive and insensitive luminophores.…”
Section: Dopant Dyes For Other Application (Partial Pressure Of Oxygen)mentioning
confidence: 99%
“…The size of the particles could be controlled at between 0.5 and 2.6 µm by adjusting the concentration of the polymerization initiator used. The particles produced were used to demonstrate the measurement of the partial pressure of oxygen in a narrow gas jet (Kimura et al [115,118]). Images of these pressure sensitive beads with a narrow particle size distribution can be seen in figure 15.…”
Section: Dopant Dyes For Other Application (Partial Pressure Of Oxygen)mentioning
confidence: 99%
“…The response time of PSPs has been described as being dependent on three important parameters: Luminescent lifetime of the luminophor, the oxygen diffusivity, and thickness of matrix layer. Kimura et al 18 found the lifetime in a previous study where it was shown that the scope of the luminophors' lifetime expands from 1 μs to 50 μs. The estimation of the 99% rise time of a thin PSP layer can be expressed as…”
Section: Introductionmentioning
confidence: 95%